(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article discusses the process of formation of written communicative competence in the first year of a language university. It describes the construction of a written text based on the analysis of the psycholinguistic features of written speech in English; the principles of constructing a methodology for teaching written speech in the first year of a language university were determined; and also clarified the goals and content of teaching writing in the first year of a language university